PENGEMBANGAN VEGETABLE LEATHER DAUN TAWA’OLOHO (Spondias pinnata) DAN RUMPUT LAUT (Eucheuma cottonii) - Amiludin, Amiludin; Wahyuni, Sri; Asyik, Nur (JURUSAN ILMU DAN TEKNOLOGI PANGAN, UNIVERSITAS HALU OLEO, 2018)
ABSTRACT The aims of this research were to investigate the effect of seaweed concentration on physicochemical characteristics andorganoleptic assessment of vegetable leather base tawa'oloho leaf. This research used Completely Randomized Design(RAL) with variation of seaweed quantity and addition of tawa'oloho leaf. The results showed that the treatment of seaweedconcentration of 3.38 g (R3) was the preferred treatment of panelists with a score of preferences on color of 3.20 (slightlylike), texture of 3.50 (like), aroma of 3.07 (slightly like) and taste of 2.82 (rather like). Selected vegetable leather had meanpercentage of elongation, thickness and solubility of 10%, 0.11% and 71.43%, respectively. So it can be concluded that theconcentration of seaweed effect on organoleptic assessment of texture and physicochemical vegetable leather with theaddtion of tawa'oloho leaf.Keywords: Seaweed, vegetable leather, Spondias pinnata. ABSTRAK Penelitian bertujuan untuk mengetahui pengaruh konsentrasi rumput laut terhadap karateristik fisikokimia dan penilaianorganoleptik lembaran vegetable leather daun tawa’oloho. Penelitian ini menggunakan Rancangan Acak Lengkap (RAL)dengan variasi jumlah rumput laut dan penambahan daun tawa’oloho. Hasil penelitian menunjukkan bahwa perlakuankonsentrasi rumput laut 3.38 g (R3) merupakan perlakuan yang paling disukai panelis dengan skor penilaian kesukaanterhadap warna sebesar 3.20 (agak suka), tekstur sebesar 3.50 (suka), aroma sebesar 3.07 (agak suka) dan rasa sebesar2.82 (agak suka). Vegetable leather terpilih memiliki nilai rata-rata persen pemanjangan, ketebalan dan kelarutan berturutturutsebesar10%,0.11%dan71.43%.Sehinggadapatdisimpulkanbahwakonsentrasirumputlautberpengaruhterhadappenilaianorganoleptikteksturdanfisikokimiavegetableleatherdenganpenambahandauntawa’oloho.Katakunci:Rumputlaut,vegetableleather,Spondiaspinnata.